Fetal Hemoglobin Research and Clinical Relevance in Sickle Cell Disease - Bjorg Gudmundsdottir; John F. Tisdale (Physiology, 2025)
Sickle cell disease (SCD) is the most common monogenic disorder, globally affecting close to eight million individuals. SCD is a devastating disease where patients suffer from extreme pain due to vaso-occlusive episodes (VOEs), end-organ damage and premature death. The burden of SCD is projected to rise significantly in the near future, making basic and clinical research to develop curative treatments even more acute. SCD was the first genetic disorder where the underlying molecular alterations were defined, an amino acid change resulting in polymerization of the sickle hemoglobin molecule and blockage of capillary vessels. One of the major findings in the field is the realization that fetal hemoglobin (HbF) expression, which is turned off shortly after birth in majority of people, can ameliorate the symptoms of SCD when it persists. Therefore, conceiving a strategy to reactivate expression of HbF in adult erythroid cells became a viable therapeutic option. In this review we provide a historical overview of the key discoveries of fetal and sickle hemoglobin research and the major clinical applications that were implemented based on those findings, including Hydroxyurea, to lessen symptoms by increasing HbF levels. We also discuss other therapeutic opportunities to treat symptoms or cure SCD.